Buku Cerita Bergambar Perjalanan Karir Kepelatihan Sir Alex Ferguson di Manchester United - Bambang Pratama Kandra; Ariusmedi Ariusmedi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
An Illustrated Storybook of Sir Alex Ferguson’s Coaching Career at Manchester United is designed to narrate the journey of one of the most prominent figures in the world of football from the United Kingdom. This project addresses the lack of engaging and inspiring reading materials for Indonesian adolescents, particularly those that present biographical content in an illustrated format. The book aims to serve as an alternative form of educational and motivational media, with the ultimate goal of fostering reading interest among young readers in Indonesia. The visual elements of the book are rendered in a semi-realistic, full-color illustration style to enhance appeal and accessibility for the target audience—teenagers. The design process utilizes the glass box method, which involves the collection of data and information from external sources. These sources include academic journals, articles, websites, films, YouTube content, autobiographical e-books, and other relevant digital platforms. Data collection is conducted to ensure a comprehensive understanding of the subject matter. Additionally, the problem-solving approach employed is based on the 5W+1H analytical framework (What, Why, Who, When, Where, and How). The final outcome of this undergraduate thesis project is a primary medium in the form of an illustrated storybook. It is further supported by a variety of promotional media such as an e-book, T-shirt, drawstring bag, X-banner, stickers, keychains, and posters.